Leather Wallet Purchasing: Quality, Price, and Advertising Influence: Pengaruh Kualitas Produk, Harga, dan Periklanan terhadap Keputusan Pembelian Dompet Kulit: Studi Kuantitatif - Fedrica Dellyanti; Dewi Komala Sari (Academia Open, 2023)
This descriptive study aimed to examine the impact of product quality, price, and advertising on purchasing decisions for leather wallets at Aris Collection, Tanggulangin Sidoarjo. The research employed a quantitative approach with a sample size of 57 respondents, selected through Simple Random Sampling. Data was collected using a questionnaire and analyzed using multiple linear regression in the SPSS Statistics version 22 program. The results revealed significant effects of product quality, price, and advertising on leather wallet purchasing decisions at Aris Collection. These findings contribute to the understanding of consumer behavior and provide implications for marketers and businesses to enhance their strategies in the competitive leather wallet market. Highlights: The study examines the influence of product quality, price, and advertising on purchasing decisions for leather wallets. Multiple linear regression analysis is employed to analyze the data collected through a questionnaire. Significant effects of product quality, price, and advertising on leather wallet purchasing decisions are identified, providing insights for marketers in the industry. Keywords: Product quality, Price, Advertising, Leather wallets, Purchasing decisions.